Parasitic Eukaryotes in a Meso-Eutrophic Coastal System with Marked Phaeocystis globosa Blooms - Christaki, Urania; Genitsaris, Savvas; Monchy, Sébastien; Li, Luen L.; Rachik, Sara; Breton, Elsa; Sime-Ngando, Télesphore (Frontiers in Marine Science, 2017)
This study explored the potential interactions and relations of the putative Symbiotic/Decomposer/Parasitic community (SymbDec) with other taxa and predominant environmental parameters in the eastern English Channel (EEC) over a 2.5 years period (32 sampling dates). The EEC is a meso-eutrophic coastal system characterized by strong repeating patterns in plankton succession with recurrent massive blooms of the Haptophyte Phaeocystis globosa preceded and followed by communities of colonial diatoms and dinoflagellate grazers. The metagenomic sequencing results of the V2-V3 hypervariable region of the 18S rRNA gene allowed an overview of the planktonic community, which consisted of 32 high-level taxonomic groups. Forty-two % of the detected OTUs belonged to potentially parasitic taxa or decomposers such as Syndiniales (MALV – MArine ALveolates), Fungi, Cercozoa, Perkinsea and others, most of which were plankton parasites. We examined the Local Similarity Analysis (LSA) network of lag delayed correlations on the 142 most abundant OTUs (> 0.1 % of the total number of reads). LSA showed that 99 OTUs had highly significant connections, involving 26 OTUs characterized as potential parasites, and 2 decomposers. The parasitic network had "small world" characteristics, rendering the assemblage more resilient to environmental change, but more susceptible to the removal of highly connected taxa. The majority of the highly connected OTUs belonged to MALV, which were mainly connected with dinoflagellates, suggesting that it might play an important role on dinoflagellate top-down control. The bloom forming P. globosa was not observed in connection with parasitic OTUs in the network. Four environmental parameters (O2, N, T, and N/P) were strongly connected with only 11 OTUs, while correlations between microbes dominated the network.